Structurally modulated formation of cyanine J-aggregates with sharp and tunable spectra for multiplexed optoacoustic and fluorescence bioimaging - Zhang, Chaobang (2024)
J-aggregation brings intriguing optical and electronic properties to molecular dyes and significantly expands their applicability across diverse domains, yet the challenge for rationally designing J-aggregating dyes persists. Herein, we developed a large number of J-aggregating dyes from scratch by progressively refining structure of a common heptamethine cyanine. J-aggregates with sharp spectral bands (full-width at half-maximum≤38 nm) are attained by introducing a branched structure featuring a benzyl and a trifluoroacetyl group at meso-position of dyes. Fine-tuning the benzyl group enables spectral regulation of J-aggregates. Analysis of single crystal data of nine dyes reveals a correlation between J-aggregation propensity and molecular arrangement within crystals. Some J-aggregates are successfully implemented in multiplexed optoacoustic and fluorescence imaging in animals. Notably, three-color multispectral optoacoustic tomography imaging with high spatiotemporal resolution is achieved, owing to the sharp and distinct absorption bands of the J-aggregates.